2011
DOI: 10.1016/j.febslet.2011.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Multiple FtsZ2 isoforms involved in chloroplast division and biogenesis are developmentally associated with thylakoid membranes inArabidopsis

Abstract: Edited by Ulf-Ingo Flügge Keywords:Chloroplast division Chloroplast morphology Thylakoid membrane FtsZ Arabidopsis thaliana a b s t r a c t Seed plants and algae have two distinct FtsZ protein families, FtsZ1 and FtsZ2, involved in plastid division. Distinctively, seed plants and mosses contain two FtsZ2 family members (FtsZ2-1 and FtsZ2-2) thus raising the question of the role of these FtsZ2 paralogs in plants. We show that both FtsZ2 paralogs, in addition to being present in the stroma, are associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…However, our novel E. coli system provides a new approach for dissecting and uncovering the chloroplast division process in the stromal side, which is topologically equivalent to the bacterial cytosol, although the possible post-translational modifications of AtFtsZs reported by Karamoko et al . 41 would not occur in bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…However, our novel E. coli system provides a new approach for dissecting and uncovering the chloroplast division process in the stromal side, which is topologically equivalent to the bacterial cytosol, although the possible post-translational modifications of AtFtsZs reported by Karamoko et al . 41 would not occur in bacteria.…”
Section: Discussionmentioning
confidence: 95%
“…In that context, sub-plastidial information retrieved from AT_CHLORO was also used to ascertain protein localization. For instance, in a recent paper (Karamoko et al, 2011), AT_CHLORO spectral count-based data reinforced immunoblot analyses showing that two FtsZ2 isoforms were associated with the thylakoid membranes. Another example concerns the CJD1 protein that influences fatty acid composition of chloroplast lipids (Ajjawi et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, we ask whether thylakoid partitioning accounts for the differences between chloroplast and nongreen plastid division. It has been reported that FtsZ proteins presented both in chloroplast stroma and thylakoid fractions, which suggests they are possibly involved in thylakoid partitioning in dividing chloroplasts [52]. In chloroplast, ARC3 interacts strongly with FtsZ1, and ARC11 interacts with MCD1 and ARC3.…”
Section: Discussionmentioning
confidence: 96%